Formulation and tribological performance of engine oil blended with various non-edible vegetable oils - Abdollah, Mohd Fadzli; Basiron, Juliana; Abdullah, Muhammad Ilman Hakimi Chua; Amiruddin, Hilmi (John Wiley & Sons, Ltd, 2023)
This present study formulated eco-friendly lubricants by combining non-edible vegetable oils with a mineral oil and investigated their efficacy on the friction and wear characteristics of four AISI 52100 chrome steel balls. Multiple formulations containing varying combinations of 0 to 100 vol% of a mineral oil SAE 15W40 (S100), castor oil (C100), and jatropha oil (J100) were prepared using the sonification technique in an ultrasonic homogeniser. A fourier transform spectrometer (FTIR) was then used to investigate the molecular vibrations of each formulation. A tribological test was also performed with a four-ball tribometer according to ASTM D4172-94 engineering standards. Finally, a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectroscope (EDX) was used to examine surface morphologies. The 80% S100, 10% C100, and 10% J100 (S80C10J10) formulation provided excellent tribological performance as it contained fatty acids composed of carbohydrates and carbonyl groups, particularly polysaccharides and glycerols.